2015
DOI: 10.1007/s00266-015-0471-2
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Sociocultural Influence: Self-monitoring and Self-awareness as Predictors of Women’s Interest in Breast Cosmetic Surgery

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the table of contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Third, this study is not exhaustive of potential variables that may protect women from body dissatisfaction and consideration of cosmetic surgery. Future studies could examine if public self-awareness, which is related to both self-compassion (Neff and Vonk, 2009) and acceptance of cosmetic surgery (Matera et al, 2015), might be a relevant mediator of the relationship between these two variables. Moreover, we used a convenience sample, so our findings are not generalizable to the entire population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this study is not exhaustive of potential variables that may protect women from body dissatisfaction and consideration of cosmetic surgery. Future studies could examine if public self-awareness, which is related to both self-compassion (Neff and Vonk, 2009) and acceptance of cosmetic surgery (Matera et al, 2015), might be a relevant mediator of the relationship between these two variables. Moreover, we used a convenience sample, so our findings are not generalizable to the entire population.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research findings (Thompson and Zuroff, 2004), the negative components were hypothesized to be related to both body dissatisfaction and acceptance of cosmetic surgery by fostering both internalization of societal standards of beauty and comparisons with the appearance of others (Hypothesis 2). We also posited a link from internalization to physical appearance comparison (Nerini et al, 2014; Matera et al, 2015; Stefanile et al, 2015), and from body dissatisfaction to acceptance of cosmetic surgery (Markey and Markey, 2009; Slevec and Tiggemann, 2010; Menzel et al, 2011; Lunde, 2013). Body mass index (BMI) was included to control for its effect, and the components of self-compassion were allowed to covary.…”
Section: The Present Studymentioning
confidence: 99%
“…Having an attractive partner could be perceived as somewhat normative, so imagining having a poorly attractive partner might direct men’s attention to appearance more than imagining having a good-looking partner. Being appearance more salient in this condition, men might become especially aware of their aspect and focus more on it; increased self-awareness could thus enhance their consideration of cosmetic surgery as a strategy to improve their physical features [ 78 ]. Such a consideration might be independent of their dissatisfaction with body fat or muscularity, as we know that men’s interest in cosmetic procedures is not necessarily related to the extent to which they are satisfied with their body weight and shape [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found that sociocultural influences are not the only significant factor for the development of attitudes towards cosmetic interventions, but rather that specific aspects of the self also play an important role. For instance, selfmonitoring and self-awareness (both private and public) had a direct effect on women's consideration of breast cosmetic surgery [19]. Other studies have also shown that the feelings about one's own looks are the key factor in deciding upon a cosmetic surgery, and that reactions to changes caused by these interventions are more positive if reasons are personal and not under the influence of the partner [20].…”
Section: Discussionmentioning
confidence: 99%